Contribution of Whole Body F-18-FDG-PET and Lymphoscintigraphy to the Assessment of Regional and Distant Metastases in Cutaneous Malignant Melanoma - Klein, M.; Freedman, N.; Lotem, M.; Marciano, R.; Moshe, S.; Gimon, Z.; Chisin, R. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: This pilot study describes use of whole body PET (WB PET) for staging of melanoma. WB PET in conjunction with lymphoscintigraphy (LS) for evaluating status of the sentinel lymph node (SLN) in primary melanoma was investigated with comparison to histopathological results. WB PET was also used both for primary and metastatic melanoma for screening for distant metastases, restaging and follow-up. Methods: Group I: 17 patients with primary cutaneous melanoma underwent LS, WB PET and SLN dissection. WB PET findings were compared with biopsy results at the SLN site and were used for screening for distant metastases. Group II: 17 patients with a history of melanoma underwent WB PET for follow-up and/or restaging. Results were confirmed or refuted by other radiological modalities or by biopsy or clinical follow-up. Results: Group I: out of 20 SLNs identified by LS in the 17 patients, 18 were negative on WB PET and 2 were positive. 19/20 WB PET findings were confirmed either by histopathology or by clinical followup (20 mo). Accuracy was 94% for the assessment of the status of the SLN. Group II: WB PET findings altered staging and treatment in 12/17 patients and confirmed the validity of treatment in 3/17 patients. Overall, in 15/17 patients (88%), WB PET had an impact on treatment strategy. Conclusion: Further studies are required to demonstrate if WB PET can become a reliable non-invasive alternative to surgery in the characterization of the SLN. WB PET is important as a baseline in primary localized melanoma and decisively impacts patient management in metastatic melanoma.
Keywords: Melanoma; sentinel lymph node; FDG; PET; lymphoscintigraphy